Influence of Digital Customer Experience, Social Media Engagement, and Brand Trust on Online Purchase Intention of Electronic Products - Umpusinga, Hasrun Afandi; Alam, Iskandar Ali; Habiburahman, Habiburahman; Barusman, Andala Rama Putra (IJBLE Scientific Publications Community Inc., 2026)
The rapid growth of online commerce has transformed consumer behavior, particularly in the electronic products sector, where purchase decisions are influenced by digital interactions, social engagement, and perceived brand reliability. This study investigates the influence of Digital Customer Experience (DCX), Social Media Engagement (SME), and Brand Trust (BT) on Online Purchase Intention (OPI) of electronic products, focusing on Brands X, Y, and Z. Using a quantitative approach, data were collected from 300 online consumers through structured questionnaires and analyzed using Structural Equation Modeling (SEM). The results indicate that all three factors have a significant positive impact on OPI, with Brand Trust exhibiting the strongest influence, followed by Digital Customer Experience and Social Media Engagement. These findings suggest that electronic brands can enhance online purchase intention by providing seamless digital experiences, fostering meaningful engagement on social media, and establishing robust trust mechanisms. The study contributes to the theoretical understanding of online consumer behavior and offers practical implications for developing effective digital marketing strategies in competitive electronic markets.